Genetic Modifiers of Systemic Lupus Erythematosus in FcγRIIB(−/−) Mice - Bolland, Silvia (The Rockefeller University Press, 2002)
FcγRIIB is a potent lupus susceptibility gene as demonstrated by the observation that mice deficient in this molecule develop spontaneous antinuclear antibodies (ANA) and fatal glomerulonephritis when on the C57BL/6 background. To determine the mechanisms underlying the epistasis displayed by this gene we have constructed hybrids between FcγRIIB(−/−) and the systemic lupus erythematosus (SLE) modifiers yaa and lpr and the susceptibility locus Sle1. Sle1 and B6.RIIB(−/−) are both physically and functionally coupled; compound heterozygotes of Sle1 and B6.RIIB(−/−) develop significant disease, while single heterozygotes display no evidence of autoimmunity or disease, indicating that these genes lie on the same genetic pathway resulting in the loss of tolerance to nuclear antigens. However, the generation of ANA in itself is insufficient to account for the severity of autoimmune disease in this model, as demonstrated by analysis of yaa and lpr hybrids. Thus, B6.RIIB(−/−)/lpr mice are protected from disease progression, despite equivalent titers of ANA. In contrast, B6.RIIB(−/−)/yaa mice have significantly enhanced disease despite reduced ANA titers. Yaa modifies the specificity and thus the pathogenicity of the B6. RIIB(−/−) ANA, by converting them to antinucleolar antibodies. In addition to these known modifier pathways, we have discovered two novel, recessive loci contributed by the C57BL/6 genome that are required for the ANA phenotype, further indicating the epistatic properties of this SLE model.